Transfer, transitions and transformations of learning - Baartman, L. K. J.; Middleton, H. E. (International Technology Education Studies, 2013)
This book explores one of the enduring issues in educational research and one of the challenges for formal education. That is, understanding the relationship between learning in one context, setting or time and a subsequent related learning experience or activity. The chapters in the book examine the issue drawing on existing theory as starting points but using each author's own research to push existing boundaries of what we know in terms of the ideas captured in the title of the book: transfer, transitions and transformations of learning. The chapters explore the issue through a range of approaches and settings including: possibilities for a concept-context approach to transfer, transfer between knowledge domains, transfer as an iterative process between contexts, transfer as boundary crossing between vocations, transfer as integration of theory and practice, transferring standards in assessment, representation in the transition from novice to expert, transformation of self through sustainability education, transforming identities of first year design and technology teachers and the role of implicit knowledge in understanding the relationship between declarative and procedural knowledge in the transition to expertise. This book should be of interest to teachers in schools and the adult education sector, research students, teacher educators, researchers and policy-makers who are involved in learning in, through or with technology.